Peran Dinas Sosial dalam Menghadapi Peningkatan Anak Jalanan di Kota Pontianak - M. Awaluddin; Febriana Driyanti Putri; Mela Sari (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
The issue of street children has become a major concern for the Social Affairs Office of Pontianak City. In 2023, the number of street children fostered by the Integrated Child Service Center (PLAT) was 29, and in 2024 this figure increased to 39. Most of these children were identified as drug users and alcohol consumers. This study aims to analyze the role of the Social Affairs Office in addressing the growing number of street children. The research employed a qualitative method with a documentation study and content analysis approach. The findings indicate that poverty, dysfunctional family conditions or divorce, and environmental influences are the main factors that drive children to live on the streets and become neglected. The Social Affairs Office of Pontianak City carries out its role through the Integrated Child Service Center (PLAT) unit, which provides guidance to street children who have undergone urine and blood tests to confirm drug use. Furthermore, according to the Pontianak City Government, effective collaboration is required between the local government, the National Narcotics Agency (BNN), and the Indonesian Child Protection Commission (KPAI) of Pontianak. It is further emphasized that prevention programs should be aligned with policies at various levels of government to reduce the number of street children. The involvement of the business sector through social responsibility, particularly via Corporate Social Responsibility (CSR) funding, is also considered crucial in addressing the issue by providing educational scholarships for street children in Pontianak City.